Mast Cells Respond to Cell Injury through the Recognition of IL-33 - Lunderius Andersson, Carolina; Enoksson, Mattias; Nilsson, Gunnar (Frontiers in Immunology, 2012)
Mast cells have been attributed several functions in both health and disease. Mast cell activation and release of inflammatory mediators are associated with the pathogenesis of several diseases, in particular that of allergic diseases. While the notion of mast cells as important, protective sentinel cells is old, this feature of the cell is not well recognized outside the mast cell field. The mast cell is a unique, multifunctional cell of our defence system, with characteristics such as wide-spread tissue distribution, expression of receptors capable of recognizing both endogenous and exogenous agents, and a capability to rapidly respond to triggering factors by selective mediator release. In this chapter, we discuss the function of mast cells as sentinel cells in the context of cell injury, where mast cells respond by initiating inflammatory responses aiming at restoring tissue function and homeostasis. In this setting, IL-33 has turned out to be of particular interest. IL-33 is released by necrotic structural cells and is recognized by mast cells via the IL-33 receptor ST2. IL-33 and mast cells probably constitute one important link between cell injury and an inflammatory response that can lead to healing, but might under other circumstances contribute to a vicious circle driving chronic inflammation.